2020
DOI: 10.1001/jamanetworkopen.2020.25095
|View full text |Cite
|
Sign up to set email alerts
|

Association of Insurance Status With Provision of Recommended Services During Comprehensive Postpartum Visits

Abstract: IMPORTANCEImproving care during the postpartum period is a clinical and policy priority. During the comprehensive postpartum visit, guidelines recommend delivery of a large number of assessment, screening, and counseling services. However, little is known about services provided during these visits. OBJECTIVE To examine rates of recommended services during the comprehensive postpartum visits and differences by insurance type. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional study included 20 071 093 weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 65 publications
3
20
0
Order By: Relevance
“…In contrast to the low prevalence of services provided during comprehensive postpartum visits in a national sample, 42 the majority of patients in our community health center setting received all recommended components of postpartum care. The most prevalent postpartum services included family planning, follow-up regarding recovery from pregnancy and birth, and documentation of infant feeding status.…”
Section: Discussionmentioning
confidence: 66%
“…In contrast to the low prevalence of services provided during comprehensive postpartum visits in a national sample, 42 the majority of patients in our community health center setting received all recommended components of postpartum care. The most prevalent postpartum services included family planning, follow-up regarding recovery from pregnancy and birth, and documentation of infant feeding status.…”
Section: Discussionmentioning
confidence: 66%
“…Many medical specialties responded to the COVID‐19 pandemic by implementing telehealth services 12,29 . Given widespread patient dissatisfaction with the pre‐pandemic model of prenatal care and recent calls by the American College of Obstetric and Gynecology to make substantial changes in the postpartum care, it may not be surprising that there has been rapid adoption of telehealth in obstetric care during the pandemic 29‐35 . The evidence base for the effectiveness and safety of telehealth in obstetric and gynecologic care made it suitable for widespread dissemination and implementation 4 .…”
Section: Discussionmentioning
confidence: 99%
“…All three topics examined in our study (contraception, depression and breastfeeding) were rated as very important and nearly always provided in a survey of clinicians who provide postpartum care [ 44 ]. Yet, a recent study examining documented postpartum visit content found that contraceptive counseling or provision occurred less than 50% of the time, while depression screening was documented in under 10% of visits, although provision of services did not vary by patient insurance status [ 27 ]. Our results suggest that experiences during the childbirth hospitalization may be another important factor predicting variation in postpartum visit content, and that further efforts to improve quality and equity in postpartum care are needed.…”
Section: Discussionmentioning
confidence: 99%
“…In prenatal care, for example, attending the recommended number of prenatal visits is insufficient for achieving good perinatal outcomes [20][21][22][23]; this finding has led to increasing interest in assessing the content and quality of prenatal care [24][25][26]. A recent study found that most recommended services were delivered at less than half of comprehensive postpartum visits, although there were few differences in provision of recommended services by whether or not the woman was insured by Medicaid [27]. Experiences of discrimination in healthcare generally or during pregnancy and childbirth specifically could affect the quality of care received in the postpartum visit by negatively impacting patient-clinician communication and adherence to recommendations and follow-up [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%